2018
DOI: 10.1016/j.envsci.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The Guarani Aquifer System, highly present but not high profile: A hydropolitical analysis of transboundary groundwater governance

Abstract: The Guarani Aquifer System, highly present but not high profile: a hydropolitical analysis of transboundary groundwater governance Introduction This article explores the governance of the Guarani Aquifer System (GAS) through the lens of critical hydropolitics and specifically through the framework of hydro-hegemony. This study is important as the GAS, which is one of the first examples of transboundary groundwater cooperation, has been studied through hydrological and geological disciplinary approaches (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…For instance, when it comes to transboundary groundwater resources, there is no formal agreement on the groundwater aquifer between Botswana, Namibia, and South Africa, but technical cooperation, promoted also by the UN through UNESCO, is very active and promising [37]. Similarly, the Guarani Aquifer System (GAS), a groundwater basin shared between Argentina, Brazil, Paraguay, and Uruguay, shows that even before the ratification of the GAS agreement, bilateral cooperation at the local level was successfully happening, for instance, in the case of the municipalities of Concordia (Argentina) and Salto (Uruguay) [38]. Regardless of the GAS preratification of the agreement, Botswana, Namibia, and South Africa would have all scored zero according to the SDG 6.5.2 Indicator.…”
Section: Either Operational Arrangement or Nothing?mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when it comes to transboundary groundwater resources, there is no formal agreement on the groundwater aquifer between Botswana, Namibia, and South Africa, but technical cooperation, promoted also by the UN through UNESCO, is very active and promising [37]. Similarly, the Guarani Aquifer System (GAS), a groundwater basin shared between Argentina, Brazil, Paraguay, and Uruguay, shows that even before the ratification of the GAS agreement, bilateral cooperation at the local level was successfully happening, for instance, in the case of the municipalities of Concordia (Argentina) and Salto (Uruguay) [38]. Regardless of the GAS preratification of the agreement, Botswana, Namibia, and South Africa would have all scored zero according to the SDG 6.5.2 Indicator.…”
Section: Either Operational Arrangement or Nothing?mentioning
confidence: 99%
“…For instance, informal technical meetings behind closed doors known as the picnic-table talks between Israeli and Jordanian officials before the 1994 peace treaty are an example of informal pre-cooperation; these talks contributed to the subsequent official water cooperation after 1994 [43,44]. An instance of informal cooperation at the municipal level is the Salto-Concordia case of the GAS, where informal cooperation continued even after the GAS project was officially concluded [38,45]; in the GAS case, the regional treaty and GAS project were initiated by communication among the scientific and epistemic communities in the region. In the case of the Disi Aquifer, which is shared between Jordan and Saudi Arabia, informal political meetings of governmental authorities used to take place regularly in the past decades [46], and brought the two governments to signing the 2015 Disi Agreement; even if it is not yet fully operational although signed and ratified [47,48], the Disi Agreement is an example of informal cooperation in the preoperational arrangement phase.…”
Section: Making Informal Formal and Technical Talks Count By Adding mentioning
confidence: 99%
“…Groundwater resources are often over-exploited for agricultural uses in the Haihe River Basin, as well as in other basins around the world, from the Middle East to South America [35][36][37][38]. Research has shown how management of transboundary groundwater resources is more likely to happen at the local level rather than at the national or transboundary level, as users have a direct interest in preserving quantity and quality of its water [39,40]. SDG 6, although not perfect, gives important guidelines and sets goals for improving the sustainable use of water resources [41,42].…”
Section: Arol Model Of Groundwater Exploitation Rate and Effective Irmentioning
confidence: 99%
“…SDG indicator 6.5.2 takes the first approach [37,40]. To strengthen SDG 6.5.2 various researchers propose either a cooperation continuum [41] or qualitative analyses, including hydropolitical assessments and discourse analyses [37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Based on relevant literature review, we identified ten Indicator 6.5.2 gaps, as discussed in this sub-section.…”
Section: Identified Policy Gaps: Sdg 652mentioning
confidence: 99%